Occurence of Metalresistant Microorganisms on Islands of the Internal Shelf of the Antarctic Peninsula - Tashyrev, A.B.; Rokitko, P.V.; Matvieieva, N.A.; Tashyreva, A.A.; Romanovskaya, V.A. (Український антарктичний журнал, 2009)
Microorganisms, superresistant to toxic metals, have been revealed in a geographical zone of internal island shelf of Antarctic peninsula (30x60 km) on islands Darboux, Lippmann, Berthelot, Cruls, Barchans, Jalour, Uruguay, Scua, Three pigs, Winter, Grotto, Galindez, Pitermann, Booth, capes Perez, Rasmussen, Tuxen (coast of Antarctic peninsula), and also on distant from them island King-George. The highest number of metalresistant microorganisms is revealed on the medium containing 1000 ppm of Cr(VI) - up to 5,0х10⁵ cells/g of soil and on the medium containing 250 ppm of Ni²⁺ – 3,0-5,0x10⁵ cells/g of soil.